A Wide Bandgap Polymer with Strong π–π Interaction for Efficient Fullerene‐Free Polymer Solar Cells. Issue 15 (3rd June 2016) - Yao, Huifeng; Yu, Runnan; Shin, Tae Joo; Zhang, Hao; Zhang, Shaoqing; Jang, Bomee; Uddin, Mohammad Afsar; Woo, Han Young; Hou, Jianhui
Abstract : A wide bandgap polymer donor PBDTS‐DTBTO is designed and synthesized, which shows an optical bandgap of 1.76 eV and strong π–π interaction. By using a low‐bandgap acceptor ITIC, power conversion efficiency over 9% is achieved in the fullerene‐free polymer solar cells (PSC) device. Furthermore, the PSC devices fabricated by PBDTS‐DTBTO:ITIC show relatively small sensitivity to variations of the active layer thickness.